Pengaruh Celebrity Endorsement, Customer Satisfaction, Viral Marketing Dan Sertifikasi Halal Terhadap Customer Loyalty (Studi Kasus pada Produk Skincare Skintific di Kota Malang) - Indriani, Ferlia; Rizal, Mohammad; Sholehuddin, Sulton (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The objective of this study is to ascertain the impact of Celebrity Endorsement, Customer Satisfaction, Viral Marketing, and Halal Certification on customer loyalty towards Skintific Skincare Malang City. The sampling technique used proportional sampling to obtain a sample of 100 respondents. The data collection method uses a questionnaire. The data analysis technique used in this research is multiple linear regression. The research results show that Celebriny Endorsement, Customer Satisfaction, Viral Marketing and Halal Certification simultaneously have a positive and significant effect on purchasing decisions. Partially, Celebrity Endorsement and Halal Certification have a positive and insignificant effect, while Customer Satisfaction and Viral Marketing have a positive and significant effect. Keywords: Celebrity Endorsement, Customer Satisfaction, Viral Marketing, Halal Certification